Akupresur Pada Acupoint SP6 Dan LI4 terhadap Tingkat Nyeri dan Lama Persalinan Kala II Di Puskesmas Rawat Inap Kota Yogyakarta - Sujiyatini Sujiyatini; Nur Djanah (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
Acupressure on acupoint SP6 and LI4 can stimulate the release of the hormone oxytocin for induction of labor and pain management during labor, childbirth and old pain management can manage with non pharmacological approaches one of them is akupresure. The purpose of this research is to explain the influence of acupressure on acupoint SP6 and LI4 against the intensity of the pain and long labor Stage II. The research is intended to explain the influence of acupressure on acupoint SP6 and LI4 against the intensity of the pain and long labor Stage II.The design used are quasi alphabets experiment with the form of the draft pre post test control group design. The samples are divided into two groups, the Group's treatment of acupressure on acupoint SP6, LI4 and acupoint and control group by the number of total respondents forty two people in Clinics Jetis, as the intervention group and in Clinics Tegalrejo as control group. Variable independent variable consists of research i.e. acupressure on acupoint SP6 and LI4 acupoint dependent variables, while covering the level of pain and labor long Stage II. The results of the research there is a significant difference between the average scale of pain between the control and intervention groups, there is a difference in themean old phase two between the intervention group and the control group. There is the influence of acupoint acupressure SP6 and LI4 against, the intensity of pain, and the old labor Stage II